Redactable blockchain and it’s implementation in bitcoin - Rajasekhar, Krovi; HarshiniYalavarthy, Sri; Mullapudi, Sravani; Gowtham, M (International Journal of Engineering and Technology, 2017)
A Blockchain is a ledger of records. It originally came from the digital currency bitcoin. Its main features are transparency and accountability. For this we use chameleon hashing concept which uses a trapdoor key. Unless the trapdoor is used it is hard to find collisions. We can create collisions only if we know the trapdoor and can rewrite the block of data with the new redacted stored files in blocks are permanently recorded and cannot be modified. To overcome this, we use the new redaction capability and expand its usefulness for enterprises and also in financial sector. This could limit uses in financial sector for the services because this must require data to be changed or smashed, coding and transaction mistakes might happen, which can be undone through redaction. An unchangeable record is not useful for the applications that area used for blockchain. Wherever the blockchain is used, either for a code or data there should be a way to redact it in unavoidable situations. The constraints for redacting a blockchain should be strict and can be done with whole block. We use this redaction concept with the bitcoin technology, which is a person-to-person digital cash system.